Effects of different electrical stimulation on depression: a protocol for systematic review and network meta-analysis - Yao, Shaoyan; Li, Song; Ran, Qinying; Zhu, Tao; Zhang, Raoting; Zhou, Lei; Zhang, Jianmei (Frontiers in Psychiatry, 2025)
ObjectiveDepression is a common mental disorder characterized by persistent depressive mood, anhedonia, and diminished interest, severely impacting patients’ quality of life and social functioning. Traditional treatments exhibit significant interindividual variability in efficacy, adverse reactions, uncertain long-term outcomes, high relapse rates upon discontinuation, prolonged treatment cycles, and substantial economic burdens. Electrical stimulation therapy represents a potential intervention, yet its efficacy and safety remain inconsistent across studies. This study aims to analyze the efficacy and safety of different electrical stimulation modalities in treating patients with depression, quantitatively assessing their comparative advantages and potential clinical benefits.MethodsWe will comprehensively search 13 Chinese and English databases including PubMed, Embase, Cochrane Library, Web of Science, Scopus, ClinicalTrials.gov, WHO-ICTRP, OpenGrey, ProQuest China National Knowledge Infrastructure, VIP Database, Wanfang Database, and China Biomedical Database. The search time will be from the establishment of each database to August 1, 2025; 2 independent reviewers will use Cochrane the Risk of Bias Assessment Tool (Second Edition) to evaluate the methodological quality and potential bias of included studies; the primary outcome indicators will be the overall effectiveness rate, Hamilton Depression Rating Scale (HDRS) score, and Self-Rating Depression Scale (SDS) score. The secondary outcome indicators are the cure rate, Patient Health Questionnaire-9 (PHQ-9) score, adverse event rate, Side Effect Rating Scale (SERS) score, and Side Effects Scale (TESS) score; STATA will be used. Software data synthesis will be performed using a random effects model for network meta-analysis to compare the effectiveness and safety of different electrical stimulation therapies. The surface under the cumulative ranking curve is also used to indicate the likelihood of benefits and harms of an intervention. The strength of the evidence will be assessed by grading the Recommendations, Assessment, Development, and Evaluation framework.JustificationThis protocol is designed to provide evidence supporting the efficacy of electromagnetic stimulation therapy in alleviating clinical symptoms in patients with depression. Furthermore, these findings will yield a theoretical foundation and actionable reference for clinicians to optimize therapeutic strategies for depression. Depression, Electrical stimulation, network meta-analysis, randomized control trial, protocol.Trial registrationPROSPERO https://www.crd.york.ac.uk/prospero/ registration number: CRD420251103264.